FENOMENA CAMPUR KODE MASYARAKAT MELAYU KUALA TUNGKAL DI MEDIA SOSIAL: KAJIAN SOSIOLINGUISTIK - Fajriani Fitri (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Medan, 2024)
Language serves as a communication tool involving verbal and written symbols to express thoughts and feelings. In the context of the Kuala Tungkal community, the use of the local Malay dialect alongside Indonesian and English creates an intriguing phenomenon of code-mixing. This study aims to analyze code-mixing in the Instagram captions of nine accounts focused on Kuala Tungkal: @hitstungkal, @tungkalbecerite, @tungkal_barometer, @tungkalvoice, @kuliner_tungkal, @tungkal_fyp, @tungkal_kite_punye, @kabarkualatungkal, and @wisatatanjabbarat_. Using a descriptive qualitative approach along with sociolinguistic theory and Muysken's (2000) concept of code-mixing, which includes insertion, alternation, and congruent lexicalization, this research finds that this language mixing is influenced by globalization and access to social media. The findings aim to provide a deeper understanding of language interaction within the local community and its impact on cultural identity and communication in the modern era.